The Linguistic Manifestation of Believability and Deception about the Illusion of Emancipation and Freedom among Amazigh Women A Feminist Critical Discourse Analysis Approach - AIT OUFELLA, Nora (l’Université de Mostaganem, 2022)
This research focuses on gender representations in the Berber feminine oral literature and it particularly examines the poetry and folktales of Kabyles who constitute the largest Berber community in Algeria. The two genres studied are different in structure, form, and content, as well as in terms of their purpose. The aim of this study is to see whether women use their oral literature to challenge the gender norms and expectations or to maintain them, through highlighting and analyzing the various gender-related themes and the recurrent representations of males and females in both genres. The researcher also analyses the discourse that was employed by women in their poems and folk stories in order to compare them and to see whether the two genres are conveying different or same messages.As the literary productions are considered as discourses, and folk literature, in general, embed the socio-cultural practices, values, and beliefs on the one hand, and as questions are raised on how the social actors mainly females are represented, the researcher based her investigation on feminist critical discourse analysis along with Bourdieu’s sociological concepts such as the habitus and the different types of capitals. The results reveal that the analyzed poems and tales are different both in content and significance. Popular expectations of the social roles of males and females are maintained in the tales in addition to some specificities of the Kabyle values that are perpetuated. On the other hand, poems are more diversified in themes and portray different types of males and females. They reveal the awareness of women about gender inequalities imposed by the socio-cultural beliefs and patriarchy. Notwithstanding, this research offers recommendations for using folk literature as a pedagogical tool in the EFL classrooms to introduce civic education with a special regard for gender and gender equality among the values to be taught to the students and future citizens
Keywords: gender representations, feminine oral productions, Kabyle literature, Kabyle women, FCDA, gender bias